FRI0248 Prediction of Therapy Response by Baseline Scintigraphic Detection of Tnfα with A Radiolabeled Anti-TNF-α in Patients with Active Peripheral Spondyloarthritis and Rheumatoid Arthritis. (10th June 2014) - Carron, P.; Lambert, B.; De Vos, F.; Van Praet, L.; Verbruggen, G.; Elewaut, D.; Van den Bosch, F.
Abstract : Background: A major challenge in the biologic era is to predict clinical response. A large variability in the level of TNFα expression has been recognized which may influence the outcome of TNF antagonism. Thus far, treatment decisions are solely based upon clinical disease activity. In this way, only 40% of rheumatoid arthritis (RA) and peripheral spondyloarthritis (pSpA) patients achieve a clinically important response (ACR50 or ASAS40). We hypothesized that in vivo assessment of TNFα by scintigraphy with 99mTc-radiolabeled anti-TNFα antibodies may be helpful to optimize and monitor the effect of TNFα blockade. This technique may facilitate "evidence-based biological therapy" by in vivo measurement in inflamed joints of a target cytokine, prior to therapeutic administration of a biologic. Objectives: To evaluate the concordance between uptake of Tc99m-labeled certolizumab pegol and clinical assessment in peripheral arthritis and dactylitis and the ability to predict response to therapy by immunoscintigraphy before starting anti TNF treatment in active RA and pSpA patients. Methods: Certolizumab pegol was conjugated with S-HYNIC and subsequently radiolabeled with Tc99m. Patients with confirmed active disease were injected with 740 MBq and whole body images and static images of hands and feet were acquired immediately following administration, 4-6 hours and 24 hours post injection. Prior to the immunoscintigraphy, patients underwent a full rheumatological examination (68-joint count, dactylitis assessment). Immunoscintigraphic findings were scored semiquantitatively (0: no uptake, 1: moderate uptake, 2: clear uptake). Two weeks later, all patients were treated with certolizumab pegol and at week 12 new clinical and biochemical evaluation was performed. Results: 11 patients were included (RA n=5, pSpA n=6). In most of the clinically involved joints of hands and feet, a marked tracer uptake was already visualized immediately following injection, with images 4-6 hours post-injection yielding the best discriminatory results of radiolabeled uptake. In pSpA patients with dactylitis, a typical scintigraphic pattern was observed with tracer uptake in both joints and the accompanying flexor tendon. There was at least a 90% concordance rate between the swollen joint count and the immunoscintigraphy. In RA patients in clinical remission at week 12 (defined by DAS28 <2.6), swollen joints at baseline showed 100% tracer uptake. In patients with only moderate response, the uptake in swollen joints at baseline was markedly lower which may be indicative for a predictive value in therapy response. All but one patients with pSpA showed clinical important improvement as measured by ASDAS. Accordingly baseline uptake in all responders was high. Interestingly the non-responder displayed no tracer uptake at all. Conclusions: Low disease activity and/or clinical remission after 12 weeks of TNF blockade in RA and pSpA is correlated to high tracer uptake at baseline in clinically swollen joints, while low/no response was associated with limited/no baseline uptake. Therefore TNF-immunoscintigraphy could offer a new tool to identify, predict and individualize good clinical responders to biological treatment. Disclosure of Interest: P. Carron Grant/research support: This research was done as an Investigator Initiated Study funded by UCB Pharma NV., B. Lambert Grant/research support: This research was done as an Investigator Initiated Study funded by UCB Pharma NV., F. De Vos Grant/research support: This research was done as an Investigator Initiated Study funded by UCB Pharma NV., L. Van Praet Grant/research support: This research was done as an Investigator Initiated Study funded by UCB Pharma NV., G. Verbruggen Grant/research support: This research was done as an Investigator Initiated Study funded by UCB Pharma NV., D. Elewaut Grant/research support: This research was done as an Investigator Initiated Study funded by UCB Pharma NV., F. Van den Bosch Grant/research support: This research was done as an Investigator Initiated Study funded by UCB Pharma NV. DOI: 10.1136/annrheumdis-2014-eular.2367